Adjustment to Chronic Illness and Disability Through an Attachment Lens : The Makings of an Attachment-Adaptation to Chronic Illness and Disability Model - Maras, Danijela (Université d'Ottawa / University of Ottawa, 2023)
Introduction: Attachment may be relevant to psychosocial adaptation to chronic illness and disability (CID) and to treatment outcomes. Research supports attachment as a transdiagnostic risk factor for both physical and mental health. Attachment plays an important role in how individuals seek and receive care, and predicts treatment outcomes. However, there is a paucity of research examining the role of attachment in CID, especially from a transdiagnostic perspective. This dissertation includes three studies that examine the role of attachment insecurity dimensions (i.e., attachment anxiety and attachment avoidance) on the process of adaptation to CID, and that attempt to better elucidate mechanisms related to group psychotherapy process and outcome for adults living with CID. The first study proposed and tested an attachment-informed model of psychosocial adaptation to CID. The second study examined treatment predictors and outcomes of a process-based group psychotherapy intervention rooted in the principles of cognitive-behavioural therapy (CBT) and acceptance and commitment therapy (ACT). The third study examined change in psychological symptoms and group cohesion across eight sessions of the group psychotherapy, assessed for a possible reciprocal symptom-cohesion relationship, and examined if pre-treatment attachment insecurity dimensions moderated change in within-person session-by-session change in symptoms, cohesion, or in the reciprocal relationship between them. Method: Participants across the three studies were recruited from The Ottawa Hospital Rehabilitation Centre (TOHRC) between September 2016 and January 2020 (prior to changes in service delivery resulting from the COVID-19 pandemic). All participants were referred to TOHRC’s outpatient psychology program by their treating physiatrist at the same institution for support with adjustment to CID. All participants completed a battery of questionnaires (see Appendices B to J) at assessment (i.e., pre-treatment) as part of standard clinical care, and to help inform psychological assessment and treatment planning. Following assessment, most participants were referred to group psychotherapy. A total of 164 patients were invited to participate in the present research and 132 (80.5 %) consented. A total of 23 groups were formed and each group comprised two to eight consenting patients (note that the number of patients per group was larger, however not all patients consented to study participation). In addition to the pre-treatment/assessment questionnaires, group participants completed a battery of questionnaires at post-treatment (see Appendices C to J), as well as weekly measures of depression, anxiety, and group cohesion (see Appendix K). In study one, the final sample included a proportion of consenting participants who completed questionnaires of interest at pre-treatment/assessment (N = 90). In study two, the sample included participant pre- and post-treatment measures (N = 109). And in study three (N = 109), the sample included participants’ weekly questionnaires as well as pre-treatment attachment scores examined as predictors of change. The sample size in studies two and three included patients who showed indications of elevated psychological symptoms at pre-treatment on a measure of depression, anxiety, and/or overall distress, as determined by established clinical cut-offs. Results: In study one, higher avoidant coping and lower health self-efficacy mediated the relationship between attachment avoidance and health-related quality of life (HRQoL). That is, individuals with higher attachment avoidance disengage at the cognitive, behavioural, and social/emotional levels in response to illness-related stress, and this has a negative impact on health self-efficacy and HRQoL. In study two, participants who completed the group therapy showed improvements in several areas from pre- to post-treatment, including HRQoL, depression, anxiety, and self-efficacy. Pre-treatment attachment anxiety was associated with more positive outcomes for anxiety, self-efficacy, and general psychological distress. Reliable change indices suggest clinically meaningful change for the majority of participants, however most did not reliably recover. In study three, participants experienced a decrease in depression and anxiety, and an increase in group cohesion across eight sessions of the group therapy. Pre-treatment attachment avoidance was a significant moderator of the association between within-person change in depression and subsequent session change in group cohesion across eight therapy sessions. That is, for individuals with lower pre-treatment attachment avoidance, a decrease in depression was associated with an increase in group cohesion at the subsequent session. Conversely, for individuals with higher pre-treatment attachment avoidance, an increase in depression was associated with a decrease in group cohesion at the subsequent session. In terms of treatment adherence in studies two and three, patients attended an average of 6.8 sessions out of a possible 8 sessions (85% adherence). Discussion: Individual differences in attachment insecurity dimensions may shape how someone contends with CID-related stressors, and how they respond to group psychotherapy. This dissertation lends further support for transdiagnostic approaches in CID and provides proof-of-concept support for a process-based ACT-CBT group therapy. Overall, results suggest that attachment is relevant to adaptation to CID and integrating principles of attachment theory with existing models of psychosocial adaptation to CID warrants further consideration in order to better tailor treatments.
Keywords: chronic illness; disability; physical rehabilitation; quality of life; psychosocial adaptation; attachment; group; group cohesion